Measles in Canada Between 2002 and 2013. (15th April 2015) - De Serres, Gaston; Desai, Shalini; Shane, Amanda; Hiebert, Joanne; Ouakki, Manale; Severini, Alberto
Abstract: Background. In 1994, Canada committed to eliminate measles by the year 2000. This report presents the epidemiology of measles in Canada between 2002 and 2013 and its implications in sustaining measles elimination. Methods. Cases included individuals reported to the Canadian Measles and Rubella Surveillance System with confirmed measles. Results. In Canada, 1171 cases of measles were reported between 2002 and 2013 (incidence 0.29 cases per 100 000 population). The annual number of cases ranged from 6 to 752. The majority of cases were unvaccinated (63%) or had an unknown vaccination status (19%). The median age of cases was 14.4 years (range, <1 to 63 years) globally and 14 years when excluding the 2011 outbreak in Quebec where 68% of the 678 cases were 10 to 19 years old. With the exclusion of this outbreak, the incidence was highest in infants (1.0 per 100 000), lower but fairly similar between 1 and 19 years of age (0.2 to 0.4 per 100 000), and there was a substantial decline between 20 and 39 years of age (0.1 per 100 000). There was a significant trend towards a greater annual number of importations over the period. Although importations resulted in no transmission sustained for ≥12 months, 5 chains of transmission had >30 cases. The effective reproductive number between 2002 and 2013 was estimated at 0.86 (95% confidence interval, .81–.92). Conclusions. Canada has maintained elimination between 2002 and 2013, but additional efforts are needed to reduce the proportion of unimmunized individuals and respond to importation events.